Effectiveness of Lockdown in Reducing the Spread of COVID-19 - Adyati Satya Puspita; Judya Sukmana; Lestari Dewi; Erina Yatmasari (Institute of Medico-legal Publications Pvt Ltd, 2021)
At the end of 2019, a mysterious outbreak appeared, forming an atypical pneumonia suspected of originatingfrom an animal market in Wuhan China. The outbreak is a new type of coronavirus which is named asCOVID-19 disease (2019 – nCoV, Novel Coronavirus). COVID 19 disease is a viral infection caused bySARS-CoV-2, namely the acute respiratory syndrome coronavirus 2 which emerged in Wuhan, China.Vaccines and antiviral drugs have not been found, meanwhile COVID-19 are prevented by using nonpharmacologicalinterventions, one of the actions taken by several countries is to create policy protocolssuch as lockdowns.The results of this study indicate that lockdown is effective in reducing the spread of COVID -19, it can beseen from the significant decrease in R0 and Rt, <1 in several countries after lockdown such as UK 0.99(0.96–1.02), Italy 0.89 (0.87–0.91), French 0.76 (0.72–0.82) and Spain 0.74 (0.71–0.78) which means thatsomeone who is infected cannot infect other people and the disease will die (disappear). The value of Rt alsoshows a consistent decline Rt to <1 (0.88) after 2 weeks of lockdown in Italy.The conclusion from this literature show that lockdowns can reduce the spread of COVID-19 which isshown by the number of incidents before and after the lockdown which has decreased to zero cases in China.The decline in cases also occurred in Europe although at the beginning of the lockdown it was not significantbut it was increasingly effective and continued to be significant after the lockdown was imposed.